The Effect of Mind Mapping Techniques on The Vocabulary Mastery Of Second Grade Students of Elementary School - Elizabeth Kusuma; aryo SP (WAHANA, 2015)
A thesis presented to Widya Mandala Catholic University in partial fulfillment of the requirement for the Degree of Master in Teaching English as a Foreign Language. English Education Department Graduate School Widya Mandala Catholic University Surabaya 2014. In this study, the writer used a quasi-experimentalnon-equivalent-groups pre-test-post-test design. The subjects of this study were the second grade students of Elementary School. The writer used two classes as the sample of this experiment. The experimental group was taught using mind mapping and another was taught using word list. Then, the writer gave a pre-test, and post-test to the two groups. Based on the calculation of the t-test, the writer found the t-observation of both groups. From the analysis of the pre-test, the writer found out that those two groups had equal ability in vocabulary mastery. From the post-test scores, the writer also found out that those two groups were not significantly different. The t-observation of the two groups was 1.26, while the t-table was 2.08. It means that the null hypothesis which says â€œthere is no significant difference between the vocabulary mastery of the second grade students who were taught by using mind mapping technique and one of those taught by using word list technique.â€ was accepted